Respuesta :

Answer:

-6

-6i

6i

6

Step-by-step explanation:

1) √4 . √-3 . √-3

[tex]$ \sqrt{4} = 2 $[/tex]

[tex]$ \sqrt{-3} . \sqrt{-3} = (\sqrt{-3})^2 $[/tex]

[tex]$ \sqrt{4} . (\sqrt{-3})^2 = 2 \times -3 = $[/tex] -6

2) √-4 . √-3 . √-3

[tex]$ \sqrt{-4} = 2i $[/tex] .

Therefore, [tex]$ \sqrt{-4} . \sqrt{-3} . \sqrt{-3} = 2. \sqrt{-1}  \times -3 = 2i \times (-3) =  $[/tex] - 6i

3) √4 . √3 . √-3

[tex]$ \sqrt{4} = 2 $[/tex]

[tex]$ \sqrt{3} . \sqrt{-3} = (\sqrt{3})^2 . \sqrt{-1} $[/tex]

[tex]$ \implies 2 \times 3i = $[/tex] 6i

4) √4 . √3 . √3

[tex]$ \sqrt{4} = 2 $[/tex]

[tex]$ \sqrt{3} . \sqrt{3} = (\sqrt{3})^2  = 3 $[/tex]

Therefore, √4 . √3 . √3 = 2 . 3 = 6